The efficiency of chitosan-feldspar-zeolite biohybrid adsorbent in treating landfill leachate - Ibrahim, Farah Nur Diyana (2017)
Landfill is a prominence method for solid waste management. However, the production of highly contaminated leachate is a major drawback of this method. The leachate causes a great impact towards human health and environment. Thus, a proper treatment is needed. One of the treatment methods, physico-chemical method such as adsorption has shown good performance in stabilizing leachate treatment. This research was carried out to develop an environmental friendly adsorbent in treating wastewater that contaminated with varied type of pollutant like leachate. In this study, newly produced adsorbent was utilized to treat landfill leachate collected from Simpang Renggam Landfill Site (SRLS). The adsorbent prepared by combining 1:1 ratio of feldspar and zeolite and bonded together with chitosan which finally produced bead shape adsorbent. Under the optimum condition of pH 5, 6 gram of adsorbent dosage,120 minutes contact time and 5 percent of leachate in adsorbate as its initial concentration, the removal of COD, ammonia nitrogen and iron is 70%, 90% and 90% respectively and its uptake capacity is 5.89mg/g, 1.61 mg/g and 0.0127 mg/g respectively. Meanwhile, the COD, ammonia nitrogen and iron adsorption isotherm study shows that the Freundlich model is the best fitting model. Concurrently, for kinetic study, Pseudo-second order kinetics is more compliance rather than Pseudo-first-order kinetics. Furthermore, the regeneration studies show that after regenerated, the removal percentage had increase about 2%- 18% which indicated that the adsorbent has the potential to be reused. Thus, from this study, it can be concluded that CFZ biohybrid adsorbent is a potential adsorbent in wastewater treatment field that is environmentally friendly.